Key aspects of leadership in business organizations under the conditions of the Covid-19 pandemic - Kiril Dimitrov (Proceedings of the 10th International Conference on Application of Information and Communication Technology and Statistics in Economy and Education, ICAICTSEE-2020, November 27-28th, 2020,, 2021)
The paper reviews emerging aspects of leadership in business organizations under the conditions of the Covid-19 pandemic as identified two levels of its realization – on an organizational one and individual one, cultural approach to leadership, pursuing leadership through human resources and appropriate communications, considering the opinions and experience of outstanding individuals in the business world.
Keywords: H12; M12; M14; Q54; 330; Corporate culture; Crisis management; Personnel management; Natural Disasters and Their Management